Economic Evaluation of Cobalt and Iron Pricing in Lateritic Nickel Ore Sales Based on Forecasted Benchmark Mineral Prices (Period II April-Period II July 2026) - Marwan Zam Mili; Muhammad Ilham Kadar (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
The pricing of lateritic nickel ore in Indonesia has traditionally been based on nickel (Ni) content alone, neglecting associated elements such as cobalt (Co) and iron (Fe), which may lead to undervaluation. This study aims to evaluate the economic impact of incorporating cobalt and iron in lateritic nickel ore pricing based on forecasted Benchmark Mineral Prices (HPM). Secondary data comprising Benchmark Mineral Reference Prices (HMA) for nickel, cobalt, and iron from Period I of May 2025 to Period I of April 2026 were utilized. Price forecasting employed the Moving Average method of order 2, selected based on the lowest Mean Squared Error (MSE), projecting prices from Period II of April to Period II of July 2026. A comparative approach between existing and proposed pricing schemes was applied. Results show that incorporating cobalt and iron significantly increases ore value, with the limonite layer rising from $21/ton to $85/ton and the saprolite layer from $47/ton to $70-75/ton. Based on volumes of 3.8 million wmt (limonite) and 3.62 million wmt (saprolite), nickel's economic potential reaches USD 60,211,426 (IDR 957,537,484,403) and USD 103,792,752 (IDR 1,650,607,831,636) respectively, while cobalt contributes USD 19,550,965 (IDR 310,917,430,537) and USD 1,978,843 (IDR 31,469,375,560). These findings confirm that a comprehensive pricing scheme encompassing all mineral constituents is essential for improving valuation accuracy and supporting equitable mineral pricing policies.